Isoterm Sorpsi Air pada Tepung Ubi Jalar Terfermentasi dengan Angkak - Yulinda Eka Ayu Rukmawati; Sri Hartini; Margaretha Novian Cahyanti (Jurnal Kimia Valensi, 2017)
The research was aimed to obtain moisture sorption curve , moisture sorption isotherm models and obtain determine the water content monoleyer of fermented sweet potato flour with red yeast rice.The moisture sorption isotherm model used are GAB (Guggenheim Anderson deBoer), BET (Brunauer Emmet Teller) and Caurie.Meanwhile, the test of modelling accuray by MRD (Mean Relative Deviation). The results showed that the water sorption isotherm curve of sweet potato flour fermented with red yeast rice Sigmoid shaped the approach of type II. The precise mathematical models are models of GAB (Guggenheim Anderson deBoer) with a value of MRD at a temperature of 30 °C, 35 °C, 40 °C respectively at 4.41%, to 2.50%, 3.37%. Moisture content of the monolayer at temperature of 30 °C, 35 °C and 40 °C in GAB model was 7.34%, 6.57%, 16.09%, BET model was 2.09%, 1.05%, 4.26%, and Caurie model was 1.41%, 1.36%, 1.42%.DOI: http://dx.doi.org/10.15408/jkv.v0i0.4814